1949
DOI: 10.1172/jci102060
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Radioiodine in the Blood 1

Abstract: Radioiodine has been used to study the function of the human thyroid gland in various ways. The quantity of radioiodine collected by the thyroid has been determined directly by in vivo measurements (Hamilton, Sole-and co-workers [1][2][3][4]; Hertz and co-workers [5] ), and indirectly by estimations from the total quantity excreted in the urine over a fixed period (Hertz and coworkers [5]; Rawson and co-workers [6,7]). The distribution of iodine in the thyroid has been studied by autoradiograms (3) or by chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0

Year Published

1949
1949
1958
1958

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…The methods employed for collections and analyses have been described elsewhere (1,5). Clearances were calculated by the method described by Berkson and associates (6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods employed for collections and analyses have been described elsewhere (1,5). Clearances were calculated by the method described by Berkson and associates (6).…”
Section: Methodsmentioning
confidence: 99%
“…the renal excretion of iodide as estimated by the renal clearance of iodide (1)(2)(3). In addition, it has been suggested that the most explicit and precise measure of the iodine-accumulating function of the thyroid gland may be the clearance of iodide by the thyroid (3,4), defined by analogy as the volume of plasma or serum cleared by the thyroid gland of its iodide content per minute, and determined from multiple observations in vivo of the thyroid itself compared with observations of serum.…”
mentioning
confidence: 99%
“…In so far as the thyroid is the most important site for the extrarenal disposal of iodide, the latter value should provide an index of the rate of iodine accumulation by the thyroid. In support of the interpretation of Keating and co-workers, McConahey and associates (15) determined the rate of disappearance of radioiodine from blood directly from measurements of samples of plasma and found good agreement with estimates of this value obtained from curves of urinary excretion by the method employed by Keating, Power, Berkson and Haines. Luellen and co-workers (5) observed that the rate constants estimated from curves simultaneously obtained from: 1) in vivo observation of radioiodine in the thyroid in counts per second; 2) measurement of radioactivity in peripheral tissues (the thigh); and 3) urinary excretion of radioiodine, all appeared to be the same as the rate of disappearance of radioiodine from blood as determined directly.…”
mentioning
confidence: 53%
“…The former they felt to be a relative quantity depending on the capacity of the thyroid and of other tissues to dispose of iodine as well as of the kidney to excrete it, and the latter they inferred to be the rate of disappearance of radioiodine from blood. McConahey and co-workers (8) The counter tube was kept in an assembly attached to a standard so that it could be raised, lowered or turned in any direction (Figure 1). The assembly consisted of a lead cylinder with a wall 16 mm.…”
mentioning
confidence: 99%
“…Six studies were made on six myxedematous patients. Studies of the blood and urine were carried out as described in previous papers (7,8). In order to place all subjects on a comparable basis as far as dosage was concerned, observations of radioactivity were expressed as counts per second per millicurie of dosage.…”
mentioning
confidence: 99%